A Case of Long-Term Survival after Checkpoint Inhibitor Pneumonitis in a Patient with Squamous Cell Lung Cancer - Hironori Ashinuma; Satoko Mizuno; Yasushi Yoshida; Masato Shingyoji (Case Reports in Oncological Medicine)
The management of grade 1 checkpoint inhibitor pneumonitis (CIP) is to withhold immune checkpoint inhibitors; however, the natural history of this condition is unknown. We herein report the case of a woman with squamous cell lung cancer who was a long-term survivor after CIP. After 4 rounds of treatment with nivolumab, a chest CT revealed a reticular pattern and ground-glass attenuation with shrinkage of the primary nodule. Nivolumab treatment was withheld without the administration of steroids. Although she remained asymptomatic, subsequent images revealed an increasing interstitial shadow until 2 months after the stop of nivolumab treatment. Thereafter, the interstitial shadow began to improve spontaneously without steroid treatment. Moreover, although the patient has not received additional therapy, disease control of lung cancer has been obtained within a follow-up period of more than 3 years. Although the exacerbation of CIP may appear on images for several months, asymptomatic cases can be followed without the administration of steroids. If the tumor had already responded prior to the onset of CIP, a favorable long-term prognosis can be expected.